The toll effect on price of anarchy when costs are nonlinear and asymmetric - Han, D.; Lo, H.; Sun, Jie; Yang, H. (Elsevier BV * North-Holland, 2008)
We examine the efficiency of the optimal tolls by establishing the bound for the price of anarchy when the levied tolls are also considered as a part of the cost functions. For linear and nonlinear asymmetric cost functions, we prove that the price of anarchy of the system with tolls is lower than that without tolls. Furthermore, we show that the total disutility caused to the users by the tolls is bounded by a multiple of the original optimal system cost.